Intracranial Bleeding After Reperfusion Therapy in Acute Ischemic Stroke - Charbonnier, Guillaume; Bonnet, Louise; Biondi, Alessandra; Moulin, Thierry (Frontiers in Neurology, 2021)
Intracranial hemorrhage is one of the most feared complications following brain infarct. Ischemic tissues have a natural tendency to bleed. Moreover, the first recanalization trials using intravenous thrombolysis have shown an increase in mild to severe intracranial hemorrhage. Symptomatic intracerebral hemorrhage is strongly associated with poor outcomes and is an important factor in recanalization decisions. Stroke physicians have to weigh up the potential benefit of recanalization therapies firstly with different risks of intracranial hemorrhage described in randomized controlled trials, and secondly with numerous risk markers that have been found to be associated with intracranial hemorrhage in retrospective series. These decisions have become quite complex with different intravenous thrombolytics and mechanical thrombectomy. This review aims to outline some elements of the pathophysiological mechanisms and classifications, describe most of the risk factors identified for each reperfusion therapy, and finally, suggest future research directions that could help physicians dealing with these complications.